2004
DOI: 10.4141/p02-118
|View full text |Cite
|
Sign up to set email alerts
|

The influence of harvest management and fertilizer application on seasonal yield, crude protein concentration and N offtake of grasses in northeast Saskatchewan

Abstract: . 2004. The influence of harvest management and fertilizer application on seasonal yield, crude protein concentration and N offtake of grasses in northeast Saskatchewan. Can. J. Plant Sci. 84: 205-212. The goal of pasture management is to match quantity and quality of herbage to the requirement of the grazing animal. The objective of this study was to examine the effects of harvest management and fertilizer application on annual and seasonal production, protein concentration and N-offtake by eight grass specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Its roots proliferate within a day of exposure to nutrient-enriched patches while a native Agropyron species showed no proliferation over a 2-wk period (Jackson and Caldwell 1989). Crested wheatgrass has a further advantage over native species by starting to grow earlier in the spring (McCartney et al 2004), allowing it to take advantage of early nutrient fluxes before the warm season C 4 natives. These competitive advantages make the control of crested wheatgrass difficult.…”
Section: Effects Of Crested Wheatgrass Onmentioning
confidence: 99%
“…Its roots proliferate within a day of exposure to nutrient-enriched patches while a native Agropyron species showed no proliferation over a 2-wk period (Jackson and Caldwell 1989). Crested wheatgrass has a further advantage over native species by starting to grow earlier in the spring (McCartney et al 2004), allowing it to take advantage of early nutrient fluxes before the warm season C 4 natives. These competitive advantages make the control of crested wheatgrass difficult.…”
Section: Effects Of Crested Wheatgrass Onmentioning
confidence: 99%
“…Herbage N concentrations are generally higher under frequent harvest, because the plants are less mature at harvest, whereas the total N uptake could be higher or lower with frequent harvesting depending on species, soil, and year [6]. Singer and Moore [7] found that N and P concentrations decreased exponentially with increasing dry matter production at similar rates for different species of perennial grasses.…”
Section: Introductionmentioning
confidence: 94%
“…In a 2-harvest system in Saskatchewan, McCartney et al [6] found 76% of the total production was from the first harvest taken during early July, with the second harvest occurring during late September. In Minnesota, forage yields of 2-harvest and 3-harvest systems, with first harvest at the green seed and heading stages, respectively, produced more forage annually over a 3-yr period than a 4-harvest system with the first harvest taken at boot stage [18].…”
Section: Forage Productionmentioning
confidence: 99%
See 2 more Smart Citations